Fábulas, educación literaria y didáctica de los valores: Leo Lionni - Llorens García, Ramón F. (Tropelías. Revista de Teoría de la Literatura y Literatura Comparada, 2015)
Desde sus orígenes, la literatura infantil y juvenil ha sido identificada con obras cuyo único objeto consistía en convertirse en simples transmisoras de enseñanzas y en las que los valores estéticos quedaban subordinados a los valores sociales. Leo Lionni dio a las fábulas un curso diferente, las actualizó al tiempo que las adaptaba a su época en forma de álbum ilustrado. Entre ellas, Frederick por su carácter polisémico, sugiere diversas lecturas según el nivel del lector y contribuye a desarrollar su competencia literaria. From its origins, Children’s literature and Young Adult’s fiction has always been identified with a kind of works whose only object was just to transmit learning, and in which aesthetic values were secondarily rated under social values. Leo Lionni gave fables a different sense, and he up-dated them at the same time as he was adapting them to his own time in the form of an illustrated album. Among them, Frederick, due to its polysemic character, suggests a number of different readings according to the reader’s level and contributes to the development of his literary competence.